3D cell culture and osteogenic differentiation of human bone marrow stromal cells plated onto jet-sprayed or electrospun micro-fiber scaffolds. (4th August 2015) - Brennan, Meadhbh Á; Renaud, Audrey; Gamblin, Anne-laure; D'Arros, Cyril; Nedellec, Steven; Trichet, Valerie; Layrolle, Pierre
Abstract: A major limitation of the 2D culture systems is that they fail to recapitulate the in vivo 3D cellular microenvironment whereby cell–cell and cell–extracellular matrix (ECM) interactions occur. In this paper, a biomaterial scaffold that mimics the structure of collagen fibers was produced by jet-spraying. This micro-fiber polycaprolactone (PCL) scaffold was evaluated for 3D culture of human bone marrow mesenchymal stromal cells (MSCs) in comparison with a commercially available electrospun scaffold. The jet-sprayed scaffolds had larger pore diameters, greater porosity, smaller diameter fibers, and more heterogeneous fiber diameter size distribution compared to the electrospun scaffolds. Cells on jet-sprayed constructs exhibited spread morphology with abundant cytoskeleton staining, whereas MSCs on electrospun scaffolds appeared less extended with fewer actin filaments. MSC proliferation and cell infiltration occurred at a faster rate on jet-sprayed compared to electrospun scaffolds. Osteogenic differentiation of MSCs and ECM production as measured by ALP, collagen and calcium deposition was superior on jet-sprayed compared to electrospun scaffolds. The jet-sprayed scaffold which mimics the native ECM and permits homogeneous cell infiltration is important for 3D in vitro applications such as bone cellular interaction studies or drug testing, as well as bone tissue engineering strategies.